Alteration of the Redox State with Reactive Oxygen Species for 5-Fluorouracil-Induced Oral Mucositis in Hamsters - Yoshino, Fumihiko (Public Library of Science, 2013)
Oral mucositis is often induced in patients receiving cancer chemotherapy treatment. It has been reported that oral mucositis can reduce quality of life, as well as increasing the incidence of mortality. The participation of reactive oxygen species (ROS) in the pathogenesis of oral mucositis is well known, but no report has actually demonstrated the presence of ROS. Thus, the purpose of this study was thus to demonstrate the involvement of ROS and the alteration of the redox state in oral mucositis using an in vivo L-band electron spin resonance (ESR) technique. An oral mucositis animal model induced by treatment of 5-fluorouracil with 10% acetic acid in hamster cheek pouch was used. Lipid peroxidation was measured as the level of malondialdehyde determined by the thiobarbituric acid reaction. The rate constants of the signal decay of nitroxyl compounds using in vivo L-band ESR were calculated from the signal decay curves. Firstly, we established the oral mucositis animal model induced by treatment of 5-fluorouracil with acetic acid in hamster cheek pouch. An increased level of lipid peroxidation in oral mucositis was found by measuring malondialdehyde using isolated hamster cheek pouch ulcer. In addition, as a result of in vivo L-band ESR measurements using our model animals, the decay rate constants of carbamoyl-PROXYL, which is a reagent for detecting the redox balance in tissue, were decreased. These results suggest that a redox imbalance might occur by excessive generation of ROS at an early stage of oral mucositis and the consumption of large quantities of antioxidants including glutathione in the locality of oral mucositis. These findings support the presence of ROS involved in the pathogenesis of oral mucositis with anti-cancer therapy, and is useful for the development of novel therapies drugs for oral mucositis.